Growth Analysis of Lac Production in Madhya Pradesh - Jaiswal, A. K.; Pal, Govind; Singh, J. P.; Patel, Bharati (Indian Forester, 2013)
District-wise and crop-wise status of lac growing districts of Madhya Pradesh have been assessed with parameters like minimum, maximum, average production and simple growth rate (SGR) for four years (2006-07 to 2009-10). The study reported that the state contributes 16 per cent production of the country; however, the growth rate during the study period was negative and to the tune of 10.1 per cent per annum. Seoni district contributed maximum in lac production (41.6 per cent) followed by Balaghat (30.6 per cent), Hosangabad (8.4 per cent) and Mandla (7.0 per cent). Strain-wise growth rate for the whole state showed that both rangeeni and kusmi lac production attained a negative growth of 5.2 and 32.1 per cent per annum. Crop-wise growth rate for the state showed that rangeeni-summer attained positive growth (12.1 per cent per annum) while rangeeni-rainy registered negative growth(37.5per cent). Similarly,both kusmi-winter and kusmi-summer crop registered negative growth rate of 34.0 and 29.9 per cent per annum respectively.Major reduction in lac production was due to loss of rangeeni-rainy crop which caused less availability of broodlac for next season.Thus less production in one season indirectly affected production of succeeding season crops also.